Norwid w Czechach. Dzieje recepcji twórczości - Kardyni-Pelikánová, Krystyna (Slavia Occidentalis, 2022)
The author describes the history of the reception of C.K. Norwid’s works in Bohemia, starting with the first references (J.V. Frič), through a discussion of the attitude of authors of “Slovanský peled” and “Moderni revue” to the poet, the milieu of Catholic writers, to finish with the translations by J. Pilař, ornamentally published in large circulation.